1982
DOI: 10.1111/j.1365-2265.1982.tb02633.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Metabolism in Hyperthyroidism

Abstract: The serum concentrations of 25-hydroxycholecalciferol (25 OH D3), 24,25-dihydroxycholecalciferol [24,25(OH)-2D3] and 1,25-dihydroxycholecalciferol [1,25(OH)2D3] were measured in twenty-one patients with untreated hyperthyroidism. Compared with control subjects, 25 OH D3 concentrations were not altered, 24,25(OH)2D3 concentrations were increased, although not significantly and 1,25(OH)2D3 concentrations were decreased (P = 0.01). Following oral carbimazole therapy, 24,25(OH)2D3 concentrations fell (P less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 21 publications
2
20
1
Order By: Relevance
“…With radiocalcium and radiophosphate tests, we have observed that the absorbed dose of 45Ca in patients with untreated hyperthyroid ism was significantly lower than in normal subjects (n = 20, 45Ca fx 0.105 ± 0.035, p < 0.001 ), whereas the absorbed dose of 32P was slightly but not significantly lower than in normal subjects (n = 18, 32P fx 0.170 ± 0.047). The cause of the diminished Ca ab sorption in hyperthyroidism remains uncer tain: recent data indicate that circulating l,25-(OH)2D3 levels are decreased [29]. But from our data, we cannot exclude that the rapid gastric emptying and the increased rate of small intestinal transit, frequently associ ated with hyperthyroidism, could play a role in Ca malabsorption in these patients.…”
Section: Hormones and The Intestinal Absorption Of Calcium And Phosphcontrasting
confidence: 48%
“…With radiocalcium and radiophosphate tests, we have observed that the absorbed dose of 45Ca in patients with untreated hyperthyroid ism was significantly lower than in normal subjects (n = 20, 45Ca fx 0.105 ± 0.035, p < 0.001 ), whereas the absorbed dose of 32P was slightly but not significantly lower than in normal subjects (n = 18, 32P fx 0.170 ± 0.047). The cause of the diminished Ca ab sorption in hyperthyroidism remains uncer tain: recent data indicate that circulating l,25-(OH)2D3 levels are decreased [29]. But from our data, we cannot exclude that the rapid gastric emptying and the increased rate of small intestinal transit, frequently associ ated with hyperthyroidism, could play a role in Ca malabsorption in these patients.…”
Section: Hormones and The Intestinal Absorption Of Calcium And Phosphcontrasting
confidence: 48%
“…Several studies have reported a high prevalence of vitamin D deficiency in selected populations including nursing home residents and persons over age 65 [8,9] . There have been few studies, however, of seasonal variations [10][11][12][13][14] in vitamin D levels in Graves' patients.…”
Section: Thyroidectomymentioning
confidence: 99%
“…There were no significant differences in serum calcium, corrected calcium, alkaline phosphatase concentrations, or thyroid function between the four seasonal periods for either female or male patients (data not shown). In all of these studies, serum 25(OH)D levels were measured in untreated patients, but one study by MacFarlane et al [13] showed serum 25(OH)D levels to be unchanged following oral carbimazole therapy.…”
Section: Laboratory Testsmentioning
confidence: 99%
“…In addition, the current literature shows that vit D is deficient in both hypo-and hyperthyroidism. However, these results are contradictory and inconclusive (19)(20)(21)(22) Vitamin D deficiency is a widespread disorder seen in approximately 30% to 50% of the adult population (25,26). It is generally due to a lack of adequate sunlight exposure and/or nutritional vit D intake (27).…”
Section: Discussionmentioning
confidence: 99%